Violation of Language Politeness and Cooperation Principles in "Mencuri Raden Saleh" Movie: A Socio-pragmatic Study - Amelia, Dinda; Musfiroh, Tadkiroatun; Waly, Muchamad Muchibbuddin (Indonesian Journal of EFL and Linguistics, 2025)
This study aims to describe the types of violations of politeness maxims and the factors influencing these violations in the movie Mencuri Raden Saleh. Using a qualitative approach, data collection techniques involved listening and noting, while data analysis employed the pragmatic pairing method refined with theoretical triangulation for validation. The research findings reveal: (1) 19 instances of violations of politeness maxims; (2) 15 instances of violations of the cooperation principle; and (3) internal and external factors influencing these violations. The study demonstrates that politeness violations play a critical role in supporting character development, building conflict, and creating tension in the storyline. Additionally, such violations are often strategically employed to achieve specific communication goals, both directly and indirectly. These findings offer valuable insights into the use of language in popular media as a reflection of social interaction and the nuanced dynamics of politeness in communication. Furthermore, this research contributes significantly to socio-pragmatic studies by highlighting the interplay between language use and cultural norms in media narratives, providing a foundation for future studies on the implications of politeness in language, cultural representation, and media discourse.